The influence of biogenic habitat created by the non-indigenous bryozoan, Amathia verticillata, on the resident marine invertebrate community in San Diego, California - Emily M. Zavacki; Nathalie B. Reyns; Jeffrey A. Crooks; Michel A. Boudrias (Aquatic Invasions)
The non-indigenous bryozoan, Amathia verticillata, has a worldwide distribution and commonly colonizes anthropogenic structures such as docks. Although widely recognized to house marine invertebrates within its structure, little is known regarding how the biogenic material produced by A. verticillata influences the marine community dynamics. The purpose of this study was to document the temporal patterns of A. verticillata and their associated marine invertebrate community in an urbanized estuary, Mission Bay, San Diego, CA, USA. We quantified A. verticillata percent cover and the abiotic conditions between July 2021–2022. The percent cover of A. verticillata varied temporally with temperature, with highest percent cover on docksides when temperatures were warmest. We also collected A. verticillata colonies of varying morphology and size to determine if abundance, density, and diversity of the marine invertebrate community associated with A. verticillata was influenced by its biogenic material and structural complexity. All invertebrates were identified to the lowest taxonomic level possible. We identified 20 families, 19 genera, and 12 organisms to species, representing 2 non-indigenous species (NIS), 2 likely NIS, 3 cryptogenic, and 5 native species. The most abundant taxonomic groups were marine amphipods, isopods, tanaids, and polychaetes. Furthermore, we identified juvenile stages and females with eggs living within A. verticillata. The invertebrate community varied significantly by A. verticillata morphotype and structural complexity. In general, there was greater invertebrate diversity in the elongated versus compact morphotype, and the invertebrate counts and diversity increased with structural complexity. Collectively, our results suggest that A. verticillata functions as a habitat-producing ecosystem engineer that may be providing an important nursery habitat for diverse groups of marine invertebrates, including other NIS, on anthropogenic structures.